Question
\( ( 5 \times 8 ) - ( 4 + 3 ) \quad ( 5 \times 8 ) - 6 + 3 \)
Ask by Hobbs Barrett. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The first expression equals 33, and the second expression equals 37.
Solution
Certainly! Let's evaluate both expressions step by step.
### Expression 1:
\[
(5 \times 8) - (4 + 3)
\]
**Step 1: Calculate inside the first parentheses**
\[
5 \times 8 = 40
\]
**Step 2: Calculate inside the second parentheses**
\[
4 + 3 = 7
\]
**Step 3: Subtract the results**
\[
40 - 7 = 33
\]
**Final Result:**
\[
(5 \times 8) - (4 + 3) = 33
\]
---
### Expression 2:
\[
(5 \times 8) - 6 + 3
\]
**Step 1: Calculate inside the parentheses**
\[
5 \times 8 = 40
\]
**Step 2: Perform the subtraction**
\[
40 - 6 = 34
\]
**Step 3: Add the remaining number**
\[
34 + 3 = 37
\]
**Final Result:**
\[
(5 \times 8) - 6 + 3 = 37
\]
---
### Summary
- \((5 \times 8) - (4 + 3) = 33\)
- \((5 \times 8) - 6 + 3 = 37\)
The difference arises due to the placement of parentheses, which affects the order of operations.
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Extra Insights
Let’s simplify those expressions step by step! First, we solve \( ( 5 \times 8 ) - ( 4 + 3 ) \): - Calculate \( 5 \times 8 = 40 \). - Calculate \( 4 + 3 = 7 \). - So, \( 40 - 7 = 33 \). Now, for the second expression \( ( 5 \times 8 ) - 6 + 3 \): - Again, \( 5 \times 8 = 40 \). - Thus, \( 40 - 6 + 3 = 34 + 3 = 37 \). So, the results are: - For the first expression: 33 - For the second expression: 37